2017
DOI: 10.1002/bjs.10333
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs of fibrosis in small intestinal neuroendocrine tumours

Abstract: Extensive abdominal fibrosis associated with clinically significant symptoms of intestinal ischaemia and/or obstructive uropathy was linked to advanced disease in patients with SI-NETs. Prompt recognition and minimally invasive intervention was effective in disease palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 24 publications
0
62
0
3
Order By: Relevance
“…In our cohort, the median OS was 8.7 years and 5-year OS was 71%. While this is comparable to OS rates for SI NETs [1, 12], a large ( n = 824) retrospective study of SI NETs from Uppsala showed that extensive fibrosis associated with intestinal ischaemia is a poor prognostic factor for survival [5]. Similarly, a recent survival analysis of all SI NETs from our centre [13] showed that the median OS was longer (10.7 years), suggesting that the subset of patients with mesenteric fibrosis may have distinct prognostic features that merit separate consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, the median OS was 8.7 years and 5-year OS was 71%. While this is comparable to OS rates for SI NETs [1, 12], a large ( n = 824) retrospective study of SI NETs from Uppsala showed that extensive fibrosis associated with intestinal ischaemia is a poor prognostic factor for survival [5]. Similarly, a recent survival analysis of all SI NETs from our centre [13] showed that the median OS was longer (10.7 years), suggesting that the subset of patients with mesenteric fibrosis may have distinct prognostic features that merit separate consideration.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to a variety of processes such as the mass effect, bowel ischaemia, or obstruction. Encasement of the superior mesenteric artery or its branches may lead to bowel ischaemia, which is associated with poor outcome [5]. Involvement of the superior mesenteric vein may lead to ascites, ectopic small bowel varices, and venous ischaemia, resulting in bowel wall oedema and, ultimately, malabsorption, malnutrition, and cachexia.…”
Section: Introductionmentioning
confidence: 99%
“…Hidrosel, varikosel, testiküler ağrı, poliüri ve artmış idrar sıklığı, bacaklarda klaudikasyon ve ödem ve kabızlık saptanabilir (11). Hastalığın yaklaşık % 10'u malignensiye sekonder RPF olduğu için bu malignensiye spesifik belirtilerle karşılaşmak olasıdır (12)(13)(14). Serimizde öz geçmişinde bir malignite hikayesi olan hasta oranı % 15 olarak saptandı.…”
Section: Discussionunclassified
“…Occasionally, distant para-aortic lymph node metastases are present and may accompany extensive retroperitoneal fibrosis, particularly in the subset of patients with NENs of small intestine origin [15]. Nevertheless, distant para-aortic lymph node metastases have previously been confirmed as an independent negative prognostic factor for survival in NENs of the small intestine [2].…”
Section: Discussionmentioning
confidence: 99%